2017
DOI: 10.1007/s10067-017-3728-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of P-glycoprotein activity on peripheral blood mononuclear cells and polymorphonuclear neutrophils to methotrexate in systemic lupus erythematosus patients

Abstract: To elucidate the relationship between P-glycoprotein activity on peripheral blood leukocytes of systemic lupus erythematosus (SLE) patients with lupus arthritis and the clinical response to methotrexate. An observational study was made in patients with SLE according to ACR criteria 1997 who had arthralgia and arthritis and received methotrexate for ≥3 months. Methotrexate responders and non-responders were compared according to the Clinical Disease Activity Index. Mononuclear cells and polymorphonuclear neutro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…La Pgp est une molécule de transport appartenant à la superfamille des transporteurs ABC (transporteurs à cassettes liant l'ATP). Elle est codée par le gène humain MDR1 (Multidrug Resistance Gen 1) [7,8]. Environ 10% du MTX sont métabolisés dans le foie [3].…”
Section: R E T R a C T E Dunclassified
“…La Pgp est une molécule de transport appartenant à la superfamille des transporteurs ABC (transporteurs à cassettes liant l'ATP). Elle est codée par le gène humain MDR1 (Multidrug Resistance Gen 1) [7,8]. Environ 10% du MTX sont métabolisés dans le foie [3].…”
Section: R E T R a C T E Dunclassified
“…Other investigations involving methotrexate and ABCB1 have mainly focused on rheumatoid arthritis and malignancy. Surprisingly, in patients with systemic lupus erythematosus, relative to methotrexate nonresponders, those that responded to methotrexate exhibited a higher ABCB1 expression level in polymorphous neutrophils and mononuclear cells [ 98 ]. By contrast, in a series of studies with subcutaneous rheumatoid nodules, no correlation was observed between ABCB1 expression and methotrexate treatment responses [ 99 ].…”
Section: Systemic Agentsmentioning
confidence: 99%
“…Intracellular accumulation of these MTX polyglutamates occurs primarily in the liver, kidney and spleen, which may persist for weeks to months [3,6]. MTX can however be transported outside the cell by the drug efflux transporter P-glycoprotein (P-gp) [7,8]. P-gp inhibitors can therefore prolong the intracellular retention of MTX [7].…”
Section: Pharmacology Of Methotrexatementioning
confidence: 99%
“…MTX can however be transported outside the cell by the drug efflux transporter P-glycoprotein (P-gp) [7,8]. P-gp inhibitors can therefore prolong the intracellular retention of MTX [7]. The plasma protein binding of MTX is approximately 50% [3].…”
Section: Pharmacology Of Methotrexatementioning
confidence: 99%